Pelatihan leadership untuk meningkatkan softskill Kelompok Tani Desa Pejengkolan - Purwati, Nani; Safitri, Lina Ayu; Widodo, Pudji; Natalia, Fransisca (Penamas: Journal of Community Service, 2023)
Pejengkolan Village Farmer Group is a farmer group formed in 2007. Farmer groups aim to boost welfare improvements for farmers in a village. Various efforts were made to self-develop the members of the farmer groups. The problem faced by the partners after the service team approached partners was the need for more leadership in each member, which impacted a lack of soul leadership and awareness to go even further. Of course, this has an impact on the development of farmer groups. This community service activity aims to provide leadership training for farmer groups in Pejengkolan Village, Padureso District, Kebumen Regency. This training program aims to inform partners about increasing the personal branding of farmer group members and fostering a spirit of leadership that benefits the organization's development. Farmer institutional development is also directed at developing farmer groups in carrying out their functions and increasing the capacity of farmer groups through cooperation in the form of networks and partnerships.